Peningkatan Hasil Belajar IPA Materi Getaran dan Gelombang melalui Metode Diskusi Kombinasi 2C B - Siti Munawaroh (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to: (1) to know the process of implementing learning that uses a combination discussion method 2C B can improve the results of science of vibration and wave material in the learners, (2) know the improvement of learning results IPA On wave vibration After a study using a combination discussion method of 2C B. The study uses class action research methods, consisting of two cycles with stages of planning, implementation, Observation and reflection. The research subject amounted to 31 students of class VIII-D MTs N 1 Yogyakarta with the method of collecting data using observations and tests. The results showed the science learning of vibration and wave material through a combination discussion method of 2C B can be received both by learners, improving enthusiasm and response in learning. The learning outcomes of learners have improved before using the average method value 65 (category less), to average value 78 (category is enough) and 90.4 (Good category) after using a combination discussion method 2C B. The submission of learning in The class increased from 17% before using the method to 70% and 97% after using a combination discussion method of 2C B.